Analisis Humor pada Film Agak Laen Karya Muhadkly Acho - Nurzen, Vanesa Amalia; Ardhianti, Mimas (GERAM (Gerakan Aktif Menulis), 2025)
Humor is an element that triggers laughter, evokes amusement, and aims to entertain. Humor can be divided into three categories: (1) personal humor, which relates to an individual's tendency to laugh at events they find funny; (2) social humor, which arises when joking with friends; and (3) humor in art, which involves various elements. This study aims to describe the use of language (language), logic (logic), form (identity), and action (action) humor in the film Agak Laen by Muhadkly Acho. This research uses a qualitative approach with a descriptive method. The data collected consists of words and sentences containing humor elements, with the data source being the film Agak Laen (2024), with a duration of 1:58:48. Data collection techniques were conducted through documentation and note-taking. The data was analyzed using the Berger (2012) approach, which includes categories of language (language), logic (logic), form (identity), and action (action) humor. The results of the study show various categories of humor in the film, such as insults, irony, sarcasm, slapstick, and others, enriching the humor elements in the film.